Two new species of the Neotropical spider genus Umuara Brescovit (Araneae, Anyphaenidae, Anyphaeninae) from Brazil - Oliveira, Luiz Fernando M.; Brescovit, Antonio D. (Zootaxa, 2015)
Two new species of the genus Umuara are described from Brazil: Umuara freddyi, from the states of Bahia, Minas Gerais and São Paulo and Umuara xingo, from the states of Ceará, Paraíba, Sergipe, Bahia, Espírito Santo, and Rio de Janeiro.